2011
DOI: 10.1016/j.nima.2011.08.051
|View full text |Cite
|
Sign up to set email alerts
|

3D printing in X-ray and gamma-ray imaging: A novel method for fabricating high-density imaging apertures

Abstract: Advances in 3D rapid-prototyping printers, 3D modeling software, and casting techniques allow for cost-effective fabrication of custom components in gamma-ray and X-ray imaging systems. Applications extend to new fabrication methods for custom collimators, pinholes, calibration and resolution phantoms, mounting and shielding components, and imaging apertures. Details of the fabrication process for these components, specifically the 3D printing process, cold casting with a tungsten epoxy, and lost-wax casting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 8 publications
0
39
0
1
Order By: Relevance
“…Mixtures of properties and the exploitation of microfabricated structures can be used to create a range of metamaterials. There is a range of special uses, such as using a large fraction of tungsten to give sufficient heavy metal content to act as shielding for x-rays [26]. It has been reported that wear on the extrusion nozzle is a significant issue when using hard fillers in plastics.…”
Section: New Materialsmentioning
confidence: 99%
“…Mixtures of properties and the exploitation of microfabricated structures can be used to create a range of metamaterials. There is a range of special uses, such as using a large fraction of tungsten to give sufficient heavy metal content to act as shielding for x-rays [26]. It has been reported that wear on the extrusion nozzle is a significant issue when using hard fillers in plastics.…”
Section: New Materialsmentioning
confidence: 99%
“…Laser sintering and power-based approaches have also been utilized [1] as has larger-scale printing using a rapidly setting masonry substance [3]. Biodegradable materials [4], imaging apertures [5], pharmaceuticals [6,7], nanocomposites [8], and microfluids [9] have all been 3D printed. The technology has been used for preserving and increasing access to historical objects (via replication) [10] and creating educational excitement [11].…”
Section: Additive Manufacturing (3d Printing)mentioning
confidence: 99%
“…In these methods, parts are fabricated by dispersing powdered metal over a molten pool of metal substrate created by laser or by melting the powder bed. In early uses, these methods were used in the making of titanium alloy frame parts for aeronautic and aerospace crafts, which are very hard to make by traditional forging and casting methods [4][5][6] . So, direct printing of metal parts brings great hope in manufacturing and it suddenly comes to be a new trend for the future.…”
Section: Introductionmentioning
confidence: 99%